A dual band leaky wave antenna based on modified substrate integrated waveguide. Issue 8 (5th June 2017) - Nazarzadeh, Fateme; Neshati, Mohammad H.
Abstract: In this article, a new leaky wave antenna (LWA) based on modified substrate integrated waveguide (SIW) is introduced. At first, the modified SIW structure is presented and it is shown that it supports propagation of quasi‐TEM with nearly uniform electric field distribution. Then, a new cell based on diagonal‐shaped slots embedded on top surface of the structure is introduced and its dispersion characteristics and its different radiation regions are determined. A LWA made of 15 unit cells is designed and a prototype of the antenna is fabricated. The proposed LWA is simulated using a software package and its radiation characteristics are also measured. It is shown that a good agreement is obtained between simulated and measured results and two frequency bands are obtained. In the frequency range of 7 GHz to 8.25 GHz, it radiates in forward region with maximum gain of 11.3 dB and scan angles from 54° to end‐fire. In addition, it radiates in backward region from −70° to broadside from 14 GHz up to 20 GHz with maximum gain of 16.47 dB. High gain, compactness, and wide scan angles are the advantages of the proposed LWA.